Pembelajaran Bahasa Arab dengan Menggunakan Model Cooperative Learning - Ida Miftakhul Jannah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
Teaching and Learning is an activity which there are two subjects “Teachers and Learners”, and it is a systematic and systemic activity. Teacher's duty is to manage the learning effectively, efficiently and positively, which is characterized by the existence of active awareness and involvement between two subjects, so that will create learning society. The teaching and learning process requires the creativity of teachers in organizing and implementing learning well. Therefore, teachers must master many models, strategies and learning methods of Arabic language, so the teaching and learning runs effectively, efficiently and fun. Cooperative learning is one of the teaching and learning models that can be applied in the process of Arabic Teaching and learning in the classroom, and it is a form of learning by way of learners learn and work in small groups collaboratively, whose members consist of four to six peoples with a structure groups that are hiterogenic. There are several types of cooperative learning models, these types can be implemented in Arabic teaching and learning, namely Student Team Achievement Division (STAD), Jigsaw, Think Pair Share (TPS) and Team group turnamens (TGT).